Histological and functional outcomes in a rat model of hemisected spinal cord with sustained VEGF/NT-3 release from tissue-engineered grafts - Xu, Zi-Xing; Zhang, Li-Qun; Zhou, Yi-Nan; Chen, Xue-Min; Xu, Wei-Hong (Artificial cells, nanomedicine, and biotechnology, 2020)
Microvascular disturbance, excessive inflammation and gliosis are key pathophysiologic changes in relation to functional status following the traumatic spinal cord injury (SCI). Continuous release of vascular endothelial growth factor (VEGF) to the lesion site was proved be able to promote the vascular remodelling, whereas the effects on reduction of inflammation and gliosis remain unclear. Currently, aiming at exploring the synergistic roles of VEGF and neurotrophin-3 (NT-3) on angiogenesis, anti-inflammation and neural repair, we developed a technique to co-deliver VEGF 165 and NT-3 locally with a homotopic graft of tissue-engineered acellular spinal cord scaffold (ASCS) in a hemisected (3 mm in length) SCI model. As the potential in secretion of growth factors (GFs), bone mesenchymal stem cells (BMSCs) were introduced with the aim to enhance the VEGF/NT-3 release. Our data demonstrate that sustained VEGF/NT-3 release from ASCS significantly increases the local levels of VEGF/NT-3 and angiogenesis, regardless of whether it is in combination with BMSCs transplantation that exhibits positive effects on anti-inflammation, axonal outgrowth and locomotor recovery. This study verifies that co-delivery of VEGF/NT-3 reduces inflammation and gliosis in the hemisected spinal cord, promotes axonal outgrowth and results in better locomotor recovery, while the BMSCs transplantation facilitates these functions limitedly.